Strain and shear stress fields analysis by means of Digital Image Correlation on CFRP to brick bonded joints fastened by fiber anchors. (1st March 2016) - Caggegi, Carmelo; Chevalier, Luc; Pensée, Vincent; Cuomo, Massimo
Highlights: An experimental study on brick reinforced by FRP and fiber anchor has been done. The displacement fields have been measured by means of Digital Image Correlation. Strains and stresses have been obtained after an interpolation of displacements. The product stiffness–thickness of the composite has been evaluated. The crack advancement during the debonding process has been described. Abstract: Recent experimental analyses have shown the high performance of the "fiber anchor" applied over FRP to substrate bonded joints to avoid the premature debonding fracture of the reinforcement. In this study, an optical non-destructive measurement method, the Digital Image Correlation, was used to describe the debonding onto the FRP reinforced surface of 36 bricks subjected to Shear Test. A series of samples not-fastened was compared to some series fastened by fiber anchor. The fields data permitted to analyze the stress transfer zone and the effective bond length and to make several considerations about the product stiffness–thickness of the FRP strip.